Atypical myopathy. (2nd May 2022) - Bates, Nicola
Abstract : Atypical myopathy is a seasonal condition of non-exertional rhabdomyolysis seen in pastured horses. It occurs in the autumn and spring from ingestion of seeds and seedlings of sycamore ( Acer pseudoplatanus ) in Europe and box elder ( Acer negundo ) in North America. The toxins hypoglycin A and its homologue methylenecyclopropylglycine are metabolised to compounds that impair lipid metabolism, which primarily affect cardiac, respiratory and postural muscles. Initial signs are reluctance to move with muscle weakness and stiffness. Common signs are pigmenturia, hypothermia and pain of varying severity. Mortality is high and many animals succumb within 2–3 days. Treatment is intensive supportive care, including nutritional support to provide alternative energy substrates and vitamin and mineral supplementation. There is no specific antidote for atypical myopathy, so prevention is key.